Risk Model for Third Hand Smoke Against Health Problems in Children in Palembang City - Amrina Rosyada; Dini Arista Putri; Nurmalia Ermi (Berita Kedokteran Masyarakat (BKM), 2020)
Introduction The cigarette smoke residue left on home furnishings, clothes and on smokers' bodies is known to have an impact on health, especially toddlers and children. In the long term this exposure triggers the incidence of cancer. Purpose This study aims to determine the risk of third hand smoke in children under five to their health problems in Palembang. Method This study used a cross sectional design in Palembang. The sample amounted to 180 toddlers who were selected using the cluster sampling method. The analysis performed was univariate, bivariate and multivariate analysis of risk factor models. Results Based on the analysis, it is known that respondents who are classified as Third Hand Smoke (THS) have a risk of 2.905 (1,341-6,296) times for experiencing health problems than those who are not classified as THS. After controlling for socio-economic variables, smoker status, gender, child's age, father's attitude, the risk of THS against health problems increased from 8,752 (2,656-28,843). Discussion It is necessary to educate the public, especially fathers, about the dangers of exposure to cigarette smoke residues for children's health problems.Keywords : Third Hand Smoke, Smoker Father, smoke residue, Health Problems